The Effectiveness of Integrating Virtual Reality and Didactic Games in Physiological Education - Farkhodovna, Salimova Sarvinoz; Odilovna, Komilova Bakhmal; Amonovich, Shamsiyev Naim (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Teaching complex topics such as homeostatic and pathophysiological processes in physiology often presents difficulties with traditional approaches. The aim of this study was to assess the impact of complex integration of virtual reality (VR) simulators and didactic games on the effectiveness of physiology education. The research was conducted with 920 biology students from four pedagogical institutes in Uzbekistan (Shahrisabz, Urgench, Namangan, Nukus). The experimental group (n=460) was taught using VR simulators such as "3D Organon" and "PhysioEx 10.0" on Oculus Quest 2 headsets and gamification platforms like Kahoot! and Socrative, while the control group (n=460) engaged with traditional methods. Advanced statistical methods including tensor decomposition, Bayesian causal analysis, and neural networks were applied to evaluate the results. The findings showed that the learning efficiency in the experimental group was 21% higher compared to the control group. Particularly notable growth was observed in students' spatial perception (effect size = 1.78), practical application skills (1.45), and digital literacy (1.73). The study proved that the synergy of VR and gamification significantly increases students' knowledge acquisition, critical thinking, and interest in science.